Review of the Panorpa wormaldi group (Mecoptera: Panorpidae), with descriptions of two new species - Wang, Ji-Shen; Suzuki, Tomoya (European Journal of Taxonomy, 2022)
Panorpa Linnaeus, 1758 is the largest genus in the scorpionfly family Panorpidae. In this paper, a taxonomic review of the Panorpa wormaldi group is provided, with two new species described from China: Panorpa fengyanga Wang & Suzuki, sp. nov. from Zhejiang, and Panorpa zhuohengi Wang & Suzuki, sp. nov. from Guangdong. The male of Panorpa implicata Cheng, 1957 is discovered and described for the first time. A distributional map and keys to species are also provided for this group. Species number in this group is updated from 17 to 19. In addition, their biogeographical and evolutionary implications are briefly discussed.